DELINEATION OF MALE GAZE IN MARGARET ATWOOD’S SURFACING - M., Christy Nivetha; K., Hema (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Literature serves as a powerful means of human expression and has long been used to challenge societal norms. Literary theory provides readers and critics with the tools to gain deeper insights into literature through close readings and an understanding of context. Theories concerning the gaze explore how looking, seeing, and being seen are represented and the implications of these acts within texts.Feminist theorist Laura Mulvey coined the term “male gaze,” which refers to how visual arts and literature portray the world and women from a masculine-heterosexual perspective. Margret Atwood’s Surfacing intricately explores the concept of the male gaze. This concept is woven into the narrative and thematic structure, as Atwood examines the dynamics of the male gaze through the protagonist’s journey. The protagonist’s struggle to understand her own identity amid the male gaze underscores the novel’s critique of how women are objectified and defined by male perspectives. Atwood uses the male gaze to explore themes of identity, autonomy and resistance. This study aims to investigate the portrayal of the male gaze in Surfacing; to examine the power dynamics between male and female characters in the novel as influenced by the male gaze; to contextualize the Male Gaze within feminist theory, particularly in relation to the objectification and surveillance of female bodies; to assess how the narrative perspective in Surfacing either reinforces or critiques the male gaze and to explore the psychological effects of the male gaze on the protagonist and other female characters in the novel.